Non performing loan: analisis kredit bermasalah di masa pandemi Covid 19 - Musta'da, Nisfi; Pramono, Nugroho Heri (Nur Science Institute, 2022)
This study aims to determine the effect of LAR, NIM, Inflation, and BI Rate on NPLs during the Covid-19 pandemic. The study population included all conventional commercial banks listed on the Indonesia Stock Exchange in 2020. The sample selection technique used was the purposive sampling method and obtained a sample of 102 observational data. The data used are secondary in the form of financial statements of conventional commercial banks of 2020. The analysis method used is the multiple linear regression method, which is processed using Eviews. The results showed that LAR and NIM had a positive effect on NPLs. In addition, inflation and the BI Rate have no effect on NPLs during the Covid-19 pandemic. Future research can also compare non-performing loans (NPLs) before and after the COVID-19 pandemic.